1974
DOI: 10.1111/j.1600-0722.1974.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced in vitro lesions in dental enamel

Abstract: \BSTRACT -Intact enamel surfaces were exposed to continuously stirred buffers which were either supersaturated or unsaturated with respect to fluorapatite and hydroxyapatite. When the buffer was supersaturated with respect to fluorapatite and unsaturated with respeet to hydroxyapatite, caries-like lesions developed. When the liquid was unsaturated with respect to both apatites, erosion-like lesions developed. The presen.'ation of the radiopaque surface layer of caries lesions was ascribed to formation of a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…When the aqueous phase is unsaturated with respect to fluorapatite a surface layer is not formed at all and the lesion developed is therefore not a caries-like lesion. It is an erosion [Larsen, 1974;Pearce, 1983].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the aqueous phase is unsaturated with respect to fluorapatite a surface layer is not formed at all and the lesion developed is therefore not a caries-like lesion. It is an erosion [Larsen, 1974;Pearce, 1983].…”
mentioning
confidence: 99%
“…The experimental background for the effect of fluoride in the caries process is that as enamel dissolves due to an undersaturation with respect to hydroxyapatite the aqueous phase remains supersaturated with respect to fluorapatite which is formed in the surface layers of the enamel [Larsen, 1973[Larsen, , 1974. The more supersaturated with respect to fluorapatite the thicker and more mineralized becomes the surface layer and the less demineralized the lesion body enamel [Larsen, 1974;ten Cate and Duijsters, 1983;Pearce, 1983]. When the aqueous phase is unsaturated with respect to fluorapatite a surface layer is not formed at all and the lesion developed is therefore not a caries-like lesion.…”
mentioning
confidence: 99%
“…For example gelatin/lactic acid [von Bartheld, 1961;Silverstone, 1967], hydroxyethyl cellulose/lactic acid [Gray, 1966], partial hy droxyapatite saturation/lactic acid [Larsen, 1974], and diphosphonate/lactic acid [Fran cis et al, 1973;Featherstone et al, 1978a] have been shown to produce subsurface le sions in human and bovine enamel with the characteristics of natural carious lesions.…”
mentioning
confidence: 99%
“…Studies on in vitro and in vivo formation of surface layer in enamel showed that pellicle is essential for formation of surface layer (60). However results from other studies revealed that pellicle did not play a crucial role in subsurface demineralization in vitro (56,87,88). Similar reports were also obtained from the in vitro experimental data of Ten Cate and Duysters (83,84), Borsboom and Arends (14), and Theuns et al (86) who found that subsurface lesion can occur even in the absence of the pellicle.…”
Section: Mechanism Of Subsurface Lesion Formation and Progressmentioning
confidence: 89%
“…Various other studies with acidic, unsaturated calcium phosphate solution by Larsen (56) and Moreno and Zahradnik (65) finally demonstrated gels were not needed for surface layer formation. The presence or absence of stirring on surface layer formation is irrelevant, although stirring affects the rate of surface layer formation (56). Studies on in vitro and in vivo formation of surface layer in enamel showed that pellicle is essential for formation of surface layer (60).…”
Section: Mechanism Of Subsurface Lesion Formation and Progressmentioning
confidence: 99%